Does the single-walled carbon nanotube affect the rate constant of binding of biotin to streptavidin? Molecular dynamics simulation perspective. (September 2019) - Soltani, Orkide; Bozorgmehr, Mohammad Reza; Momen-Heravi, Mohammad
The interaction of biotin and streptavidin in the presence and absence of a carbon nanotube was studied by molecular dynamics simulation. With respect to the Arrhenius dependence of the rate constants with temperature, those of streptavidin–biotin complex formation (k 1 ) and streptavidin–biotin complex dissociation (k − 1 ) were calculated from molecular dynamics simulation trajectories. Nanotube has reduced the amount of and k 1 and k 1 . However, the biotin position in streptavidin does not change much. The results obtained from MMPBSA calculations show that the contribution of the van der Waals forces to both systems (in the absence and presence of the nanotube) was greater than that of electrostatic forces. The presence of the nanotube also led to the reduction of van der Waals and electrostatic forces in the interaction of biotin with streptavidin. However, this reduction was greater for electrostatic forces. In the absence of a nanotube, there are four hydrogen bonds between streptavidin and biotin, which are related to the residues Ser27, Tyr43, Ser45 and Ser88. In the presence of the nanotube, the hydrogen bonding of biotin with Ser45 is removed.